APPLICATION OF THE DRILL AND PRACTICE METHOD TO INCREASE READINESS AND LEARNING ACHIEVEMENTS (Study in English Language Subjects at SMP Negeri 06 Lebong) - Fitri Handayani; Nina Kurniah (UNIB Press, 2019)
This research purpose to describe: (1) methods of drill and practice in improving students' readiness to learn English; (2) Drill and practice methods in improving learning achievement; (3) The effectiveness of applying drill and practice methods can improve students' readiness and learning achievement. The research method used is Class and Experimental Action Research. The research subjects were students of Class VIII SMP Negeri 06 Lebong. The technique of collecting data uses tests and observations. The data analysis used was descriptive qualitative and quantitative descriptive. Based on the results and discussion of this study, it can be concluded that: (1) the application of drill and practice methods can improve the readiness of learning English. In Cycle 1 the average student learning readiness was 18.02 in the Good category, increasing to 19.78 in categories both in Cycle 2 or increased by 1.76. In Cycle 3 it increased again to 21.53 in the Good category or increased by 1.75 from Cycle 2; (2) Application of drill and practice methods can improve learning achievement in English. There is an increase in the value of the pretest to posttest with an average of 15.50; (3) Application of drill and practice methods to effectively improve the readiness and learning achievement of English. In Cycle 1 there were 60% of students' learning readiness in the good category and in Cycle 2 it increased to 70% and increased again to 97% in Cycle 3.